The Problems of Sharia Investment in Indonesia from The Perspective of Maqashid Al-Sharia - Purbaningrum, Ivana Rosa; Luthfia, Nadira; Nasim, Arim (Islamic Research, 2024)
This study examines investment instruments in Indonesia from an islamic perspective, focusing on their compliance with Maqashid Al-Shariah and Islamic capital market regulations. It also explores public preceptions of the halal status of Islamic capital market product. The methodology used is a qualitative approach with a literature review. The study reviews 200 journal articles, selecting 32 relevant journal and 2 books for analysis. The findings show that Islamic investments must adhere to the five key elements of Maqashid Al-Shariah: protection of religion, life, intellect, lineage, and wealth. Investments that fail to meet these criteria may not be considered fully compliant with Shariah, despite legal recognition. Regulations by the OJK and supported by the DSN-MUI provide a sufficient legal framework, but Shariah principles are often blended with conventional ones due to the influence of Pancasila ideology. The study also reveals mixed public opinions regarding the Islamic capital market, with many questioning whether products labeled as "Shariah" truly meet halal and Shariah principles. This skepticism is compounded by the absence of specific laws regulating the Islamic capital market, highlighting a gap between legality and morality. The study emphasizes the need for clearer policies distinguishing between Shariah and conventional principles and the importance of enhancing public literacy on Shariah-compliant investments.